2018
DOI: 10.1177/1043454218819452
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: A Pilot Program to Understand and Meet the Needs of Pediatric Patients and Families as They Transition Off Cancer-Directed Therapy

Abstract: As a result of advances in curative therapies, more than 80% of children and adolescents diagnosed with cancer are expected to survive into adulthood (Jemal, Siegel, Xu, & Ward, 2010; Noone et al., 2017). This unique population may experience long-term physical and psychosocial sequela including chronic health conditions (CHCs), high levels of distress, poor health-related quality of life, and unmet psychosocial needs (Ness et al., 2008). Late effects of treatment may affect multiple organ systems including re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…Further, findings support further study of psychosocial screening and intervention for childhood cancer patients during transition off treatment within a family context. Consistent with previous literature, 30 , 32 findings indicate that family functioning plays a role in patient HRQL and highlight the importance of assessing family factors as part of psychosocial screening 31 . Future studies would benefit from incorporating measures of illness uncertainty, which has been shown to impact both parent and child HRQL, 33 to further understand associations between family functioning and youth adaptation at this time.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Further, findings support further study of psychosocial screening and intervention for childhood cancer patients during transition off treatment within a family context. Consistent with previous literature, 30 , 32 findings indicate that family functioning plays a role in patient HRQL and highlight the importance of assessing family factors as part of psychosocial screening 31 . Future studies would benefit from incorporating measures of illness uncertainty, which has been shown to impact both parent and child HRQL, 33 to further understand associations between family functioning and youth adaptation at this time.…”
Section: Discussionsupporting
confidence: 79%
“…Even though family distress and burden generally decrease over time following a cancer diagnosis, 30 results are consistent with other studies confirming the relationship between family factors and patient HRQL across the cancer treatment continuum 6 ,. 16 The transition off cancer treatment is a critical time period to examine these associations, because it is marked by fewer guidelines and more ambiguity than the roadmaps families follow on treatment and during survivorship 31 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the study indicated that the majority of the participants found the transition visit and materials to be helpful, and they recommended that all survivors and caregivers should receive the transition visit materials immediately after treatment ends (58%), during treatment (17%), or several months after treatment ends (17%). Many participants demonstrated limited knowledge about their potential late effects based upon the treatment that they received and how long they needed follow-up care [10].…”
Section: Introductionmentioning
confidence: 99%